2010
DOI: 10.1016/j.ijhydene.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in binary and ternary Mg-based alloys: A comprehensive experimental study

Abstract: Hydrogen storage in binary and ternary Mg-based alloys : A comprehensive experimental study Kalisvaart Mg-Al-Fe, the properties are clearly worse compared to the other ternary combinations.These differences are explained by considering the properties of all the different phases present during cycling in terms of their hydrogen affinity and catalytic activity. Based on these considerations, some general design principles for Mg-based hydrogen storage alloys are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 33 publications
2
47
1
Order By: Relevance
“…Thus, the absorption time to reach the hydrogen saturation in the second and third cycle for Mg 65 Cu 10 Al 15 MM 10 alloy is lower than for the Mg 65 Cu 25 MM 10 alloy. The absorption time is observed to decrease from the second to the third cycle for both alloys, which is in agreement with a general behaviour of H-sorption properties in Mg alloys 31,32 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the absorption time to reach the hydrogen saturation in the second and third cycle for Mg 65 Cu 10 Al 15 MM 10 alloy is lower than for the Mg 65 Cu 25 MM 10 alloy. The absorption time is observed to decrease from the second to the third cycle for both alloys, which is in agreement with a general behaviour of H-sorption properties in Mg alloys 31,32 .…”
Section: Resultssupporting
confidence: 88%
“…These alloys were tested to three consecutive cycles of hydrogen absorptiondesorption. It was found that the rate of the first absorption cycle (activation) is low, which is usual for Mg alloys 31 . The sluggish rate during the activation cycle can be related to the presence of an oxide layer on the surface of the sample, which must be broken to start the hydrogenation through the volume of the material 4 .…”
Section: Resultsmentioning
confidence: 96%
“…After 10 cycles, 90% of the total capacity is absorbed within 10 seconds, which is similar to what was observed for other Mg-TM cosputtered films. 9 Hydrogen sorption measurements cannot distinguish the individual contributions of surface dissociation, diffusion and phase transformation to the 'overall' kinetics. Therefore, an in situ technique with high spatial resolution is required to separate bulk (diffusion, nucleation) and surface (dissociation) effects in real-time.…”
mentioning
confidence: 99%
“…Among these additives, some transitional metals (Barkhordarian et al 2003;Czujko et al 2006), their oxides (Mao et al 2010) and halides (Ma et al 2009) provide good catalytic effects. Since a single additive does not provide enough catalytic power (Kalisvaart et al 2010), several additives working together improve the materials' hydrogen storage abilities, with promising results . Adding binary catalysts to Mg is a hot topic, while ternary catalysts in Mg are rarely reported.…”
Section: Introductionmentioning
confidence: 99%